Grain-boundary-rich polycrystalline monolayer WS2 film for attomolar-level Hg2+ sensors - Lixuan Liu (Nature Portfolio, 2021)
Here, the authors report the controlled growth of polycrystalline WS2 films with high density of grain boundaries to realize surface plasmon Hg2+ ion sensors exhibiting attomolar sensitivity and enhanced selectivity.